Chronic inhibition of angiotensin converting enzyme lowers blood pressure in spontaneously hypertensive rats by attenuation of sympathetic tone: The role of enhanced baroreflex sensitivity - Behuliak, Michal; Bencze, Michal; Boroš, Almos; Vavřínová, Anna; Vodička, Martin; Ergang, Peter; Vaněčková, Ivana; Zicha, Josef (Biomedicine & pharmacotherapy, 2024)
Spontaneously hypertensive rats (SHR) are characterized by sympathetic hyperactivity and insufficient parasympathetic activity, and their high blood pressure (BP) can be lowered by long-term inhibition of the renin-angiotensin system. The aim of our study was to determine the influence of chronic inhibition of angiotensin converting enzyme (ACE) by captopril on cardiovascular regulation by the sympathetic and parasympathetic nervous system. Implanted radiotelemetric probes or arterial cannulas were used to measure mean arterial pressure (MAP), heart rate (HR), and arterial baroreflex in adult SHR and Wistar-Kyoto (WKY) rats under basal or stress conditions. MAP and the low-frequency component of systolic blood pressure variability (LF-SBPV, marker of sympathetic activity) were greater in SHR than in WKY rats. Under basal conditions chronic captopril treatment reduced both parameters more effectively in SHR, and the same was true during acute restraint stress. HR was similar in control rats of both strains, but WKY rats showed greater heart rate variability (HRV), indicating higher parasympathetic activity. Captopril administration increased HR in both strains, whereas HRV was decreased only in WKY. Chronic captopril treatment improved the impaired baroreflex-HR control in SHR by increasing the sensitivity but not the capacity of vagal arm of arterial baroreflex. Captopril treatment attenuated BP changes elicited by dimethylphenylpiperazinium (DMPP, agonist of nicotinic acetylcholine receptors), especially in SHR, indicating that sympathetic nerve transmission is facilitated by angiotensin II more in hypertensive than in normotensive animals. Thus, chronic ACE inhibition improves baroreflex sensitivity and lowers BP through both central and peripheral attenuation of sympathetic tone.
Keywords: Animals; Baroreflex; hypertenze; Sympathetic Nervous System; Captopril; potkani inbrední WKY; inhibitory ACE; Angiotensin-Converting Enzyme Inhibitors; Rats, Inbred WKY; krevní tlak; Radiotelemetry – Systolic blood pressure variability – Heart rate variability – Arterial baroreflex – Ganglionic neurotransmission – Captopril; srdeční frekvence; Hypertension; sympatický nervový systém; Male; krysa rodu Rattus; potkani inbrední SHR; baroreflex; mužské pohlaví; zvířata; Blood Pressure; Heart Rate; Rats; Rats, Inbred SHR; kaptopril